Klippel-Trenaunay and Parkes-Weber syndromes: two case reports - Chagas,Carlos Alberto Araujo (2017)
Abstract Parkes-Weber syndrome is a congenital vascular disease that comprises capillary, venous, lymphatic, and arteriovenous malformations. Although Parkes-Weber syndrome is a clinically distinct entity with serious complications, it is still frequently misdiagnosed as Klippel-Trenaunay syndrome, which consists of a triad of malformations involving the capillary, venous, and lymphatic vessels, without arteriovenous fistulas. Both syndromes are generally diagnosed with Doppler ultrasound and confirmed by magnetic resonance angiography. The aim of this study is to describe one case of Klippel-Trenaunay syndrome, in a 36-year-old patient, and one case of Parkes-Weber syndrome, in a 21-year-old patient. We review the literature in order to discuss the possible causes and consequences of these diseases related to venous hypertension and angiodysplasia, taking a clearer approach to their differences, and discussing their treatment.